Análise do custo efetividade de um Serviço de Atenção Domiciliar - Borges Júnior, Laerte Honorato (2018)
Introducion: Home Care (HC) is defined by actions of health promotion, prevention, treatment, rehabilitation and palliation, which are carried out at home, with security and guarantee of continuity of care and articulated with other points of the health care network. The Home Care Service (HCS) is a supplementary or substitute service for outpatient care or hospitalization. Due to several factors, HC has been developing as a new tecnoassistential model for health, among them the demographic changes occurred, the new morbidity and mortality profile with the increase of the chronic conditions, the increase in the prevalence of chronic-degenerative diseases, technology, the need to promote access to health services and increase the rotation and optimization of hospital beds, as well as concern for the quality of life of users and their families. Given that, in order for HC to legitimize itself as a treatment strategy, it still needs to be qualified, strengthened and legitimized as a health care modality that helps produce other forms of care, more humanized, resolute, focused on the integrality and needs of users, producing autonomy and determining better cost- effectiveness. Objective: To analyze the cost effectiveness of an HCS and to characterize the public user of the service. Methods: Retrospective observational and analytical study of the medical records of users served between August 2014 and September 2016. Data were collected to analyze the epidemiological profile, the effectiveness, through the origin of the request, complexity, outcome, hospital admissions and prolonged hospitalizations and the fixed and variable costs of HCS and hospital admission in medical clinic beds and compare with the cost of care with the hospital. Results: analyzed 2,008 medical records, 46.8% male and 53.2% female; 69.2% above 60 years. The monthly mean of prehospital admission was 78.4 ± 7.3% and post-hospital admission 21.6 ± 7.3%, the complexity was HC1 46.2 ± 14.2%, HC2 51.7 ± 13.7% and HC3 2.1 ± 1.6%. Regarding the outcome, the rate of high 15.8 ± 0.03%, mortality rate 5.0 ± 0.01%, rate of increase in relation to the total number of attended 62.2% and death 18.5 %, the total death in the household 53.2%. Hospital admissions increased by 38% in 2014 and 17% in 2015. In terms of costs, the figures indicated that the cost of home care is 21.5 times lower than hospital care. Conclusion: HCS was effective considering a higher prehospital admission and because it contributed to increase hospitalization in the network, also, showed good turnover, even with a higher prevalence of elderly dependent and high death rate. In addition to having a lower cost when compared to hospital care.